Semantic Stability is More Pleasurable in Unstable Episodic Contexts. On the Relevance of Perceptual Challenge in Art Appreciation - Muth, Claudia; Raab, Marius H.; Carbon, Claus-Christian (Frontiers in Human Neuroscience, 2016)
Research in the field of psychological aesthetics points to the appeal of stimuli which defy easy recognition by being “semantically unstable” but which still allow for creating meaning—in the ongoing process of elaborative perception or as an end product of the entire process. Such effects were reported for hidden images (Muth & Carbon, 2013) as well as Cubist artworks concealing detectable—although fragmented—objects (Muth, Pepperell, & Carbon, 2013). To test the stability of the relationship between semantic determinacy and appreciation across different episodic contexts, 30 volunteers evaluated an artistic movie continuously on visual determinacy or liking via the Continuous Evaluation Procedure (CEP, Muth, Raab, & Carbon, 2015). The movie consisted of five episodes with emerging Gestalts. In the first between-participants condition, the hidden Gestalts in the movie episodes were of increasing determinacy, in the second condition, the episodes showed decreasing determinacies of hidden Gestalts. In the increasing-determinacy group, visual determinacy was rated higher and showed better predictive quality for liking than in the decreasing-determinacy group. Furthermore, when the movie started with low visual determinacy of hidden Gestalts, unexpectedly strong increases in visual determinacy had a bigger effect on liking than in the condition which allowed for weaker Gestalt recognition after having started with highly determinate Gestalts. The resulting pattern calls for consideration of the episodic context when examining art appreciation.